Cross theorem for separately real-analytic functions: Cross theorem for separately real-analytic functions - Alimardon, Atamuratov; Kamol, Rasulov (The Journal of Analysis, 2025)
The present work is devoted to the study of R -analyticity with respect to the set of variables of separately R -analytic functions. In the paper, it is proved real analyticity with respect to the set of variables, out of some pluripolar set, of the separately R -analytic functions.